Particulate matter 2.5 promotes HIF-1α-associated autophagy and epithelial–mesenchymal transition in 3D retinal pigment epithelial spheroids - Da Hye Kim; EunJin Bang; Hyun Hwangbo; Min Yeong Kim; Seon Yeong Ji; Hyesook Lee; Su Hyun Hong; Gi Young Kim; JaeHun Cheong; Yung Hyun Choi (Toxicology, 2026)

Hematology-centered characterization of systemic physiological alterations during viral haemorrhagic septicemia virus (VHSV) infection in olive flounder (Paralichthys olivaceus) - Dong-Jin Lim; Su-Mi Shin; Seok-Ju Lee; Da-Seul Lee; Jin-Young Kim; Sung-Ju Jung; María del Mar Ortega-Villaizan; Myung-Hwa Jung (Fish & Shellfish Immunology, 2026)

An enhanced YOLO-based deep learning framework for automated structural defect inspection in complex backgrounds - Zheyu Liu; Di Su; Youqi Zhang; Da-Wei Lin; Zhen Sun (Engineering Structures, 2026)

Hematology-centered characterization of β-glucan-mediated disease trajectory modulation during rock bream iridovirus (RBIV) infection - Su-Mi Shin; Da-Seul Lee; Seok-Ju Lee; Dong-Jin Lim; Myung-Hwa Jung (Fish & Shellfish Immunology, 2026)

Gecko tail regeneration-inspired composite hydrogel scaffolds with “socket-plug” architecture for dynamically programmed repair of infected bone defects - Minglang Zou; Yi Tang; Yongming Wang; Ling Mo; Menghuan Wang; Qing He; Zhenjin Xu; Liu Su; Pengfei Wang; Fang Luo; Da Huang; Jiewei Luo; et al. (Chemical Engineering Journal, 2026)

Mechanochemical Fabrication of UiO-66-Supported Nilotinib Polymorphs for Drug Delivery - Junjie Peng; Youqin Wang; Jianghao Yuan; Mingkang Xu; Da Wu; Bokai Kong; Zhijie Zhang; Xiangjun Shi; Weike Su (Journal of Pharmaceutical Innovation, 2026)

Ghost carbonate in Archean granitoids marks a geodynamic transition in the Mesoarchean - Ya-Wen Zhang; Shui-Jiong Wang; Hao Wang; Bin Su; Béatrice Luais; Yu Wang; Hui-Min Yu; Da Wang; Stephen F. Foley; Xian-Hua Li (Lithos, 2026)

Two newly isolated compounds from Hansenia weberbaueriana and their anti-inflammatory potential - Jie Li; Su Hu; Li Huang; Li-Lian Zhao; Li-Jun Huang; Wei-Jun Dong; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Natural Product Research, 2026)

A previously undescribed 3,4-secodammarane derivative from Ailanthus altissima - Yu-Sha Shi; Li-Lian Zhao; Li Huang; Su Hu; De-Feng Peng; Zhuo-Hong Li; Yun Deng; Da-Le Guo (Natural Product Research, 2026)

A dual-functional single-crystalline layer boosts operational stability of organic light-emitting diodes - Gao-Da Ye; Guan-Ran Wang; Xue-Peng Wang; Su-Heng Li; Nai-Qi Wang; Hu Zhang; Yu-Ting Huang; Lingjie Sun; Yajing Sun; Fangxu Yang; Jin-Bei Wei; Yue-Feng Liu; et al. (Science Bulletin, 2026)

Investigation of the Fenton reaction of CIP@Fe3O4 and its polishing characteristics on single-crystal SiC - Da Hu; Jiabin Lu; Liyun Su; Huaian Yi; Enchi Xue (Journal of Environmental Chemical Engineering, 2026)

Machine learning-enhanced UAV multispectral remote sensing for monitoring rice leaf area index across critical growth stages - Chao Su; Zaiying Ling; Liwang Han; Yanmin Shuai; Jianguang Wen; Xingwen Lin; Haifeng Tang; Alexandre Maniçoba da Rosa Ferraz Jardim; Hoi Leong Lee; Xuguang Tang (Precision Agriculture, 2026)

Microfluidic investigation on multiphase interaction behavior and carbon dissolution sequestration mechanisms during CO₂ injection in high-water-cut deep reservoirs - Xue Zhang; Qi’an Da; Chenxi Duan; Bin Huang; Cheng Fu; Dian Zhang; Lei Li; Yuliang Su (Chemical Engineering Journal, 2026)

Development of Novel Host-Associated Low-Temperature Probiotics (HALP) Tailored to Aquaculture Applications - Su-Jeong Lee; Young-Sun Lee; Yu-Ri Kim; Mi-Hyeon Jeon; Da-In Noh; Seong-Mok Jeong; Kang-Woong Kim; Eun-Woo Lee; Won Je Jang (Probiotics and Antimicrobial Proteins, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Plasma-induced microcracked stretchable strain sensor array for multifunctional wireless sensing in smart tires - Xiaopeng Du; Xiaona Wang; Shaojie Yuan; Da Chen; Hongen Qu; Xiaoqian Hou; Bing Yao; Chuang Su; Xingyu Ma; Yuhao Cai; Tong Zhang; Ge Song; et al. (Chemical Engineering Journal, 2026)

Structural Performance and Weight-Efficiency Trade-Offs of Bulb and Angle Stiffeners in Imperfection-Sensitive Plate Buckling and Collapse - Myung-Su Yi; Da-Bin Jung; Joo-Shin Park (Journal of Marine Science and Engineering, 2026)
This study presents a mechanics-based comparison of the buckling and ultimate strength behavior of stiffened plates reinforced with bulb-type and built-in angle stiffeners, with particular emphasis on the trade-off between structural performance and weight efficiency. Although these stiffener types are commonly treated as equivalent when designed to provide the same sectional moment of inertia, their nonlinear collapse behavior under realistic loading conditions has not been sufficiently quantified. To address this gap, a two-stage finite element framework is employed, consisting of linear eigenvalue buckling analysis to identify imperfection-sensitive modes, followed by geometrically and materially nonlinear imperfection analysis (GMNIA) to capture post-buckling behavior and ultimate strength. High-fidelity three-dimensional solid models incorporating classification-society-based material properties are used to simulate axially compressed stiffened plates representative of jack-up rig Living Quarter structures. The results demonstrate that, while both stiffener types exhibit comparable elastic buckling resistance, their nonlinear responses differ in terms of stiffness degradation, stress redistribution, and collapse localization. Importantly, the angle stiffener achieves an ultimate strength comparable to that of the elastically equivalent bulb stiffener while requiring less material, thereby exhibiting superior weight efficiency. These findings indicate that elastic equivalence alone is insufficient for optimal stiffener selection and highlight the necessity of nonlinear, imperfection-sensitive assessment in the design of lightweight and high-performance marine structures.

The transcription factor BRN2 confers cadmium tolerance by regulating SAM1 expression in Arabidopsis - Su Li; Jing Huang; Jia Qi Li; Chuan Jin Shan; Ren Fang Shen; Da Li Zeng; Jin Chen; Xian Jiao Guan; Xiao Fang Zhu; Ting Wu Liu; Yong Gang Xu (Plant Science, 2026)

Hematology-centered physiological remodeling of black seabream (Acanthopagrus schlegelii) under gradual water temperature fluctuations - Seok-Ju Lee; Su-Mi Shin; Jae-Hyun Sim; Da-Jeong Yoo; Eunju Kim; Myung-Hwa Jung (Fish & Shellfish Immunology, 2026)

Morphometric and Cytological Characterisation of Enlarged Basophilic Cells in Rock Bream ( Oplegnathus fasciatus ) During Rock Bream Iridovirus ( RBIV ) Infection - Seok‐Ju Lee; Su‐Mi Shin; Dong‐Jin Lim; Da‐Seul Lee; Myung‐Hwa Jung (Journal of Fish Diseases, 2026)
Rock bream iridovirus (RBIV), a member of the Megalocytivirus genus, causes systemic infection and high mortality in rock bream ( Oplegnathus fasciatus ). Although enlarged basophilic cells are diagnostically relevant, their developmental trajectory and structural changes remain insufficiently characterised. This study provides the first quantitative morphometric and cytological characterisation of these cells, focusing on cytoplasmic and nuclear alterations, multinucleation and anucleation. Following oral administration of virus‐containing tissue (200 mg; 6.12 × 10 8 MCP copies), enlarged basophilic cells appeared from 11 dpi, only in fish with viral loads > 10 6 copies/mg. Among 1664 cells analysed, mononucleate (A‐1), multinucleated (two nuclei) (A‐2), multinucleated (three nuclei) (A‐3) and anucleate (B) types were identified. Mononucleate cells predominated at lower viral loads (over 83.1%), whereas anucleate cells comprised > 39.9% at higher loads. Exceptionally large cells with cytoplasmic axes of 50–60 μm were frequently observed. Cell and nuclear dimensions increased progressively with viral load, and multinucleate and anucleate forms predominated in fish with higher viral burdens. A schematic sequence of morphological progression from nuclear enlargement to nuclear loss is proposed as a working model, based solely on morphological evidence. Our study provides the first quantitative description of RBIV‐induced enlarged basophilic cells and establishes a morphometric framework for future investigations into RBIV pathogenesis.

Efficacy of copper alloy coatings in controlling Ichthyophthirius multifiliis infections: a sustainable alternative for freshwater aquaculture - Zi-Hong Guo; Wen-Hao Wu; Ming-Da Chen; Zi-Jian Long; Jian-Cheng He; Jia-Hao Zhang; You-Lu Su; Biao Jiang (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Hematology-centered homeostatic immunity confers durable resistance to rock bream iridovirus (RBIV) in rock bream (Oplegnathus fasciatus) - Su-Mi Shin; Min-Sung Kim; Da-Seul Lee; Dong-Jin Lim; Myung-Hwa Jung (Fish & Shellfish Immunology, 2026)

Effective production of biosyngas from biomethane over spatially confined Ni catalyst with captured CO2 - Su-Ji Kim; Yeon Jeong Yu; Sung-Bin Choi; Gwan-Joong Park; Da-Bin Kang; Byung Sun Yoon; Ye-Eun Jeon; Min-Young Kim; Jeong-Chul Kim; Young-Kwon Park; Chang Hyun Ko (Bioresource Technology, 2026)

Distribution and correlation of trace elements in Eurasian otters (Lutra lutra) from South Korea - Da Sol Park; Eun Jae Park; Dahye Shin; Rihyun Kim; Bongkyun Kim; Yongsun Hyun; Hee-Jong Kim; Kyu-Vin Kim; Chang Uk Chung; Dong-Hyuk Jeong; Jong Seung Kim; Ju Yeong Park; et al. (Environmental Science and Pollution Research, 2026)

E-cigarette vapor alters gut microbiota composition in zebrafish - Thi Ngoc Mai Dong; Delbert Almerick T. Boncan; Carl Andersen Macaraeg Tan; Da-Wei Liu; Hsin-Yu Sun; Ting-Wei Huang; Chen Hsu; Kuo-Chang Chu; Zulvikar Syambani Ulhaq; Keng Po Lai; Douglas Robert Drummond; Yukiko Ogino; et al. (Science of The Total Environment, 2026)

Bacteriophage emulsion for prevention of Salmonella contamination in eggshells - Su Jin Jo; Sang Guen Kim; Sib Sankar Giri; Sung Bin Lee; Jae Hong Park; Mae Hyun Hwang; Da Sol Park; Eun Jae Park; Se Chang Park (International Journal of Food Microbiology, 2026)

Effect of papaya leaf extract on growth performance, skin mucosal immune responses, liver enzymes, disease resistance, and tight junctions of Cyprinus carpio - Sib Sankar Giri; Jin Woo Jun; Sung Bin Lee; Su Jin Joo; Mae Hyun Hwang; Jae Hong Park; Da Sol Park; Eun Jae Park; Venkatachalam Sukumaran; Se Chang Park (Fish & Shellfish Immunology, 2026)

Detection of H9N2 Avian Influenza Virus in commercial raw meat-based diets for dogs and cats in South Korea - Chang-Tae Kim; Dong-Wook Lee; Da-Won Kim; Ji-Yun Kim; Ye-Jin Lee; Hee-Su Kim; Seulgi Bae; Jung-Hoon Kwon (Veterinary Microbiology, 2025)

Divergent drought-induced suppression on vegetation and associated feedbacks: Satellite-based observations in 2022 across the Yangtze River basin, China - Lei Han; Yanan Chen; Chaoyang Wu; Li Yao; Ying Wang; Chao Su; Xuan Li; Alexandre Maniçoba da Rosa Ferraz Jardim; Thieres George Freire da Silva; Xuguang Tang (Journal of Hydrology, 2025)

Bioconversion and characteristics of the rebaudioside D-like compound by glucosyltransferases combination - Hye-Jin Kim; Ok Cheol Kim; Seong-Jin Hong; Hye-Jin Kang; Da Eun Jang; Boo-Su Park; Jeong-Yong Cho; Young-Min Kim (Food Chemistry, 2025)

Effect of Illicium verum Hook.f. (star anise) extract on the modulation of systemic and mucosal immunity in Aeromonas hydrophila-aggravated Cyprinus carpio - Sib Sankar Giri; Hyoun Joong Kim; Subrata Saha; Jae Hong Park; Sung Bin Lee; Su Jin Joo; Mae Hyun Hwang; Da Sol Park; Eun Jae Park; Kihae Ra; Sukumaran Venkatachalam; Se Chang Park (Fish & Shellfish Immunology, 2025)

Reducing toxicity of atrazine using subcritical hydrolysis technology and investigation the hydrolysis mechanism - Shuo Pan; Huaiyu Zhou; Shuang Wu; Qing Wang; Jingru Bai; Da Cui; Junting Su (Environmental Science and Pollution Research, 2025)

Exploring hypoxia-triggered edema in sea cucumbers: Molecular perspectives on environmental stress - Da Huo; Bayden Russell; Fang Su; Botao Liu; Libin Zhang; Hongsheng Yang; Mary A. Sewell; Lina Sun (Aquaculture, 2025)

Assessing 3-D variability of ultrafine particle using a Geo-AI modelling approach: A case study in Zhunan-Miaoli, Taiwan - Chia-Wei Hsu; Yinq-Rong Chern; Jun-Jun Su; Pei-Yi Wong; Aji Kusumaning Asri; Candera Wijaya; Yu-Cheng Chen; Shih-Chun Candice Lung; Ta-Chih Hsiao; Tee-Ann Teo; Yi-Liang Shih; Chih-Da Wu (Environmental Pollution, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Functional characterization of RNAi candidate target genes in Monolepta hieroglyphica (Motschulsky) for potential pest control applications - Xu Chen; Ning Fu; Qingxuan Xu; Chun Zhang; Su Wang; Da Xiao (Journal of Asia-Pacific Entomology, 2025)

Baricitinib-loaded separable microneedle array patch (S-MAP) based on hyaluronic acid for alopecia areata therapy - Da In Jeong; Song Yi Lee; Sungyun Kim; Su-Min Jo; HeeSeon Yang; Jieun You; ChaeRim Hwang; Ji Won Huh; Yeoung Eun Choi; Wonjun Jo; In-Jeong Choi; Hae-Jin Hu; et al. (Carbohydrate Polymers, 2025)

Particulate matter 2.5 stimulates pyroptosis and necroptosis via the p38 MAPK/Akt/NF-κB signaling pathway in human corneal epithelial cells - Da Hye Kim; Hyesook Lee; Min Yeong Kim; Hyun Hwangbo; Seon Yeong Ji; EunJin Bang; Su Hyun Hong; Gi Young Kim; Sun-Hee Leem; Dongryeol Ryu; JaeHun Cheong; Yung Hyun Choi (Toxicology, 2025)

High-precision age constraint for the Xiyingzi Bed of the Jiufotang Formation in western Liaoning, Northeast China - Li-Jun Zhang; Si-Yu Song; Shu-An Ji; Su-Chin Chang; Jahandar Ramezani; Fei Gao; Bo Wang; Hai-Chun Zhang; Da-Ran Zheng (Palaeoworld, 2025)

Environmental impact of brine and cooling water mixing ratios on marine water quality and biota: a comparative field study - Hanwen Song; Changsheng Peng; Xiaoqing Zhang; Junrui Cao; Da Song; Bo Su (Environmental Monitoring and Assessment, 2025)

Dual structure Brønsted sites activated carbon beads solid acid enhances the highly efficient synthesis of HMF: From batch to continuous - Wei-Yao Yang; Meng Wen; Hong-Da Zhang; Ya-Qiao Tian; Shi-Chao Su; Yu Lang; Zhi-Ping Zhao; Le Sang (Chemical Engineering Journal, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Modeling supports the implementation of urban greening as a response to the challenges of sustainable spatial planning - Eun Sub Kim; Jung Hee Hyun; Na Yeon Kim; Su Jeong Heo; Da Seul Kim; Dong Kun Lee (Journal of Environmental Management, 2025)

Assessment of nuclear desalination in a small modular reactor using membrane distillation - Gabriel C.G.R. da Silva; Carolina P. Naveira-Cotta; Kleber M. Lisboa; Renato M. Cotta; Jian Su (Annals of Nuclear Energy, 2025)

Experimental study on transient electromagnetic conductivity logging in cased well - Yong-Jin Shen; Yuan-Da Su (Applied Geophysics, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Research and software development of compression buckling for laser-welded stiffened plates based on physics-informed neural networks - Zhenfei Guo; Lijie Su; Zongzhe Man; Zhenkun Lei; Hao Jiang; Da Liu; Jiangfan Zhou; Xiao Wei (Ocean Engineering, 2025)

Recruitment of beneficial microbes and differential metabolites promoted Pb transport in Salix integra Thunb. after inoculation with Bacillus megaterium B6 - Ping Chen; Jian Zhou; Guang Cai Chen; BeiBei Su; Qian Wang; Da Zhuang Huang; Xiao Yun Niu (Plant and Soil, 2025)

Tree-level carbon stock estimations across diverse species using multi-source remote sensing integration - Qing Li; Jia Yin; Xiaoxin Zhang; Dalei Hao; Matheus Pinheiro Ferreira; Wenhui Yan; Ye Tian; Da Zhang; Shen Tan; Sheng Nie; Tianyu An; Xiaoyao Li; et al. (Computers and Electronics in Agriculture, 2025)

Model tests study of multi-layer geosynthetic-reinforced pile-supported embankments and evaluation of analytical design models - Da Zhang; Guangqing Yang; Ting Li; Peng Xu; Penghui Su (Transportation Geotechnics, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

Inhibition effect of Botrytis cinerea and quality preservation of grape by Bletilla striata polysaccharide - Da Li; Yanli Zheng; Xuemei Han; Haiyu Ji; Xiaoxiang Su; Zhou Yuan; Kejing Yang; Xiaoyu Jia (Physiological and Molecular Plant Pathology, 2025)

Unraveling phase-dependent variations of viral community, virus-host linkage, and functional potential during manure composting process - Zhengyuan Zhou; Songfeng Liu; Muhammad Saleem; Fei Liu; Ruiwen Hu; Hualong Su; Da Dong; Zhiwen Luo; Yongjie Wu; Yan Zhang; Zhili He; Cheng Wang (Bioresource Technology, 2025)

Curculigoside Regulates Apoptosis and Oxidative Stress Against Spinal Cord Injury by Modulating the Nrf-2/NQO-1 Signaling Pathway In Vitro and In Vivo - Yu Hou; Chaolun Liang; Lili Sui; Yang Li; Kai Wang; Xing Li; Kunrui Zheng; Haitao Su; Dianweng Xie; Dingkun Lin; Da Guo; Le Wang (Molecular Neurobiology, 2025)

Dual carbon isotopes constrain the sources and age variations of terrestrial organic carbon in the middle Okinawa Trough since the last deglaciation - Mengna Chen; Chenglong Su; Shuang Wang; Da-Wei Li; Hailong Zhang; Li Li; Guangxue Li; Bingyuan Xu; Jishang Xu; Meixun Zhao (Global and Planetary Change, 2025)

Evaluation of acute, repeated dose 28-day and 13-week oral toxicity and genotoxicity of a standardized fraction (HemoHIM) from Angelica gigas, Cnidium officinale, and Paeonia lactiflora - Ju Gyeong Kim; Su-Bin Bak; Gyoung-Deuck Kim; Han-Sol Choi; Da-Ae Kwon; Ha-Young Kim; Dong-Won Son; Jang-Hun Jeong; Byung-Woo Lee; Hyo-Jin An; Hak Sung Lee (Toxicological Research, 2025)
HemoHIM is a functional food ingredient comprising a triple herbal combination of extracts from Angelica gigas Nakai, Cnidium officinale Makino, and Paeonia lactiflora Pallas. It was developed to aid the recovery of impaired immune function. Although it is widely used to treat various immune disorders in Korea, its potential toxicity has not been extensively investigated. Therefore, a comprehensive study was conducted to assess the safety of HemoHIM, including acute oral dose toxicity, 28-day and 13-week repeated-dose toxicity, and genotoxicity. To evaluate its safety profile, the dose was increased to 2,000 mg/kg/day, which corresponds to the dose limit for acute toxicity as per the Organization for Economic Cooperation and Development Test Guideline 423. No abnormal findings were observed at the higher doses. For the 28-day and 13-week repeated-dose toxicity studies, HemoHIM was administered at doses of 500, 1,000, and 2,000 mg/kg/day to examine subchronic toxicity in male and female rats. No test item-related clinical signs or mortality was observed at any of the tested doses. Gross pathology, hematology, blood chemistry, and histopathology evaluations further supported the safety of HemoHIM. Therefore, the NOAEL of HemoHIM was considered to be at 2,000 mg/kg/day for both sexes of rats. Bacterial reverse mutation tests, a chromosome aberration test in human peripheral blood lymphocytes, and a mouse micronucleus test were conducted to determine the genotoxicity of HemoHIM, which revealed that HemoHIM was non-mutagenic and non-clastogenic. Collectively, these findings provide valuable evidence to support the safe use of HemoHIM as a functional food ingredient.

Three-dimensional Heterogeneity and Intrinsic Plasticity of the Projection from the Cerebellar Interposed Nucleus to the Ventral Tegmental Area - Chen Wang; Si-Yu Wang; Kuang-Yi Ma; Zhao-Xiang Wang; Fang-Xiao Xu; Zhi-Ying Wu; Yan Gu; Wei Chen; Ying Shen; Li-Da Su; Lin Zhou (Neuroscience Bulletin, 2025)

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

Utilizing fly ash from coal-fired power plants to improve the utilization of incineration fly ash resources and reduce toxicity - Xiaodong Ma; Tingshu He; Yongqi Da; Fuyun Su; Renhe Yang (Journal of Environmental Management, 2024)

Towards sustainable fruit production: Identifying challenges and optimization strategies - Liangquan Wu; Xiaojun Yan; Jiayi Huang; Xiuzhu Xu; Siwen Zhang; Shilei Cui; Xiaohui Chen; Zhixiong Zeng; Shuangyong Huang; Yingzhe Zeng; Yibin Weng; Bingkun Lu; et al. (Agricultural Systems, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Development of Extubation Success Prediction Model for Mechanically Ventilated Patients with Spontaneous Cerebellar Hemorrhage - Yao Jiang; Yue Yu; Jing Fan; Lei Zhang; Yang Ye; Ying-hong Hu; Li-da Su (The Cerebellum, 2024)

Electric field induced molecular orientation to construct the composite polymer electrolytes with vertically aligned ion diffusion pathways for stable solid-state lithium metal batteries - Yuanjun Zhao; Mengqiu Gao; Yanyang Qin; Xinyu Da; Xuetian Deng; Xin Jia; Kai Xi; Yaqiong Su; Shujiang Ding; Qiang Rong; Xiangpeng Kong; Guoxin Gao (Chemical Engineering Journal, 2024)

Functional plants supporting predatory ladybirds in a peach orchard agroecosystem - Changbing Wu; Séverin Hatt; Da Xiao; Song Wang; Su Wang; Xiaojun Guo; Qingxuan Xu (Arthropod-Plant Interactions, 2024)

Iron species and sulfur isotopic compositions of authigenic pyrite in deep-sea sediments at southern Hydrate Ridge, Cascadia margin (ODP Leg 204): implications for non-steady-state depositional and diagenetic processes - Chenhui Liu; Shao-Yong Jiang; Xin Su; Xiaopeng Bian; Hai Ding; Da Li; Tao Yang (Frontiers in Marine Science, 2024)
Two accretionary sediment sequences from Sites 1245 and 1252 recovered during Ocean Drilling Program (ODP) Leg 204 at southern Hydrate Ridge were investigated to explore the response of geochemical partitioning of iron and sulfur isotopic composition of authigenic pyrite to non-steady-state depositional and diagenetic scenarios. Five iron species were characterized by a modified sequential extraction procedure that covers almost all iron-bearing minerals in sediment cores, including: (1) iron-bearing carbonates, mainly siderite; (2) ferric (hydr)oxides, probably ferrihydrite and/or lepidocrocite; (3) magnetite; (4) iron-bearing silicates; and (5) pyrite. Highly reactive iron has been accumulated for a long-term steady-state history and its pyritization, to varying degrees, is limited by availability of dissolved sulfide. This causes pyrite and siderite occurred in the same sedimentary layer and shows an inverse relationship between their concentrations. From this, their proportions to highly reactive iron can be chosen for evaluating the degree of sulfidization. A significant change in sulfur isotopic composition of pyrite (-42.4 to +16.8‰ VCDT) indicates that the steady-state conditions are dramatically limited, where the δ 34 S values higher than -20‰ may result from an upward shift of SMT zone close to the seafloor or a sudden, massive depositional event. To explain the downcore sulfidization effects and pyrite δ 34 S values, we developed two categories of conceptual scenarios based on variations in sedimentation rate and methane flux. The geochemical features similar to those derived from each scenario were searched in the sediment columns and the non-steady-state events behind the scenarios were proved to be consistent with the real observations. Thus, iron species and pyrite δ 34 S values can be regarded as a proxy to differentiate different non-steady-state depositional and diagenetic controls on the sedimentary record.

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Establishing quality evaluation standards for pomelo fruit: The role of harvesting time and appearance characteristic - Xiaojun Yan; Muhammad Atif Muneer; Mengting Qin; Jie Ou; Xiaohui Chen; Zhiyuan He; Yedong Liu; Zhihan Cheng; Da Su; Rongrong Liu; Liangquan Wu (Postharvest Biology and Technology, 2024)

A comparative study on the nutritional composition, protein structure and effects on gut microbiota of 5 fermented soybean products (FSPs) - Xinyu Miao; Honghong Niu; Mubai Sun; Xin Dong; Mei Hua; Ying Su; Jinghui Wang; Da Li (Food Research International, 2024)

Explainable geospatial-artificial intelligence models for the estimation of PM2.5 concentration variation during commuting rush hours in Taiwan - Pei-Yi Wong; Huey-Jen Su; Shih-Chun Candice Lung; Wan-Yu Liu; Hsiao-Ting Tseng; Gary Adamkiewicz; Chih-Da Wu (Environmental Pollution, 2024)

Evaluation of acute, 28-day, 13-week repeated dose oral toxicity and genotoxicity of a herbal extract (HemoHIM G) from Angelica sinensis, Ligusticum chuanxiong, and Peaonia lactiflora - Su-Bin Bak; Hansol Choi; Gyoung-Deuck Kim; Ju Gyeong Kim; Da-Ae Kwon; Ha-Young Kim; Dong-Won Son; Jang-Hun Jeong; Byung-Woo Lee; Hyo-Jin An; Hak Sung Lee (Toxicological Research, 2024)
HemoHIM G is a functional food ingredient composed of a triple herbal combination of Angelica sinensis , Ligusticum chuanxiong , and Paeonia lactiflora , to improve impaired immune function. Considering the pharmacological benefits of its constituent herbal components, HemoHIM G is anticipated to have various health benefits; however, its toxicity has not been thoroughly evaluated. Here, we conducted a comprehensive study to assess the safety of HemoHIM G in terms of acute oral toxicity, 13-week repeat-dose toxicity, and genotoxicity. In the oral acute toxicity study, Sprague–Dawley rats were orally administered a single dose of HemoHIM G at 5000 mg/kg/day, the limit dose for the acute study. No abnormal findings or adverse effects were observed in this study, as confirmed by gross pathology. A 13-week repeated-dose toxicity study was conducted with HemoHIM G at doses of 1250, 2500, and 5000 mg/kg/day to examine the subchronic toxicity in both male and female rats after 28 days of dose-range finding study. No test substance-related clinical signs or mortality was observed at any of the tested doses. Gross pathology, hematology, blood chemistry, and histopathology were within normal ranges, further supporting the safety of HemoHIM G. Therefore, the NOAEL of HemoHIM G was considered to be at 5000 mg/kg/day for both sexes of rats. Bacterial reverse mutation tests, a chromosome aberration test in human peripheral blood lymphocytes, and a mouse micronuclei test were conducted to identify the potential genotoxicity of HemoHIM G. HemoHIM G is non-mutagenic and non-clastogenic. Collectively, these findings provide valuable evidence for the safe use of HemoHIM G as a functional food ingredient.

Iodine Acetonitrile as a Drinking Water Disinfectant Showed a Potential Toxic Effect on Organism - Ya-Ping Li; Jie-Wen Cai; Pin-Ying Su; Shi-Ming Xie; Jia-Xuan Lai; Zi-Ru Xian; Jing-Da Qiao (Water, Air, & Soil Pollution, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Mitigating life-cycle environmental impacts and increasing net ecosystem economic benefits via optimized fertilization combined with lime in pomelo production in Southeast China - Xiaojun Yan; Yifei Ma; Kunpeng Kong; Muhammad Atif Muneer; Lijun Zhang; Yadong Zhang; Zhihan Cheng; Ziwei Luo; Changcheng Ma; Chaoyuan Zheng; Wenhao Yang; Jiuxin Guo; et al. (Science of The Total Environment, 2024)

Performance Assessment of an Exhaust Gas CO2 Absorption (EGCA) System Installed on a 1.075-MW HiMSEN 5H22CDF Engine - Jin-Su Kwak; Da Hee Jung; Gyeol Ko; Jin Gyu Kwon; Sang Hoon Kim; Jae-Hoon Jee; Do Yun Kim (Fuel, 2024)

A unique subseafloor microbiosphere in the Mariana Trench driven by episodic sedimentation - Jiwen Liu; Da-Wei Li; Xinxin He; Ronghua Liu; Haojin Cheng; Chenglong Su; Mengna Chen; Yonghong Wang; Zhongsheng Zhao; Hanyue Xu; Zhangyu Cheng; Zicheng Wang; et al. (Marine Life Science & Technology, 2024)
Hadal trenches are characterized by enhanced and infrequent high-rate episodic sedimentation events that likely introduce not only labile organic carbon and key nutrients but also new microbes that significantly alter the subseafloor microbiosphere. Currently, the role of high-rate episodic sedimentation in controlling the composition of the hadal subseafloor microbiosphere is unknown. Here, analyses of carbon isotope composition in a ~ 750 cm long sediment core from the Challenger Deep revealed noncontinuous deposition, with anomalous 14 C ages likely caused by seismically driven mass transport and the funneling effect of trench geomorphology. Microbial community composition and diverse enzyme activities in the upper ~ 27 cm differed from those at lower depths, probably due to sudden sediment deposition and differences in redox condition and organic matter availability. At lower depths, microbial population numbers, and composition remained relatively constant, except at some discrete depths with altered enzyme activity and microbial phyla abundance, possibly due to additional sudden sedimentation events of different magnitude. Evidence is provided of a unique role for high-rate episodic sedimentation events in controlling the subsurface microbiosphere in Earth’s deepest ocean floor and highlight the need to perform thorough analysis over a large depth range to characterize hadal benthic populations. Such depositional processes are likely crucial in shaping deep-water geochemical environments and thereby the deep subseafloor biosphere.

The associations between high-levels of urine benzophenone-type UV filters (BPs) and changes in serum lipid concentrations - Qi Chen; Qianyu Chen; Guanyong Su; Da Chen; Zhen Ding; Hong Sun (Chemosphere, 2024)

The therapeutic efficacy of silver loaded rhenium disulfide nanoparticles as a photothermal agent for cancer eradication - Sesha Subramanian Murugan; Won Hur; Seong Eun Son; Han Been Lee; Chang Hyeon Ha; Su Jeong Lee; Se Hwa Cheon; Do Hyeon Kim; Sung Min Jeon; Da Young Choi; Jayachandran Venkatesan; Gi Hun Seong (Journal of Photochemistry and Photobiology B: Biology, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Advances on micro/nanoplastics and their effects on the living organisms: A review - Xinlin Zhao; Shuaishuai Gao; Da Ouyang; Su Chen; Caisheng Qiu; Huajiao Qiu; Zhaoming Chen (Science of The Total Environment, 2023)

Feasibility study of storing CO2 in the ocean by marine environmental impact assessment - Da Hee Jung; Gyeol Ko; Jin-Su Kwak; Do Yun Kim; Seul Gi Jeon; Seungkwan Hong (Science of The Total Environment, 2023)

A Pore-Scale Model for Electrokinetic In situ Recovery of Copper: The Influence of Mineral Occurrence, Zeta Potential, and Electric Potential - Kunning Tang; Zhe Li; Ying Da Wang; James McClure; Hongli Su; Peyman Mostaghimi; Ryan T. Armstrong (Transport in Porous Media, 2023)
Electrokinetic in-situ recovery is an alternative to conventional mining, relying on the application of an electric potential to enhance the subsurface flow of ions. Understanding the pore-scale flow and ion transport under electric potential is essential for petrophysical properties estimation and flow behavior characterization. The governing physics of electrokinetic transport is electromigration and electroosmotic flow, which depend on the electric potential gradient, mineral occurrence, domain morphology (tortuosity and porosity, grain size and distribution, etc.), and electrolyte properties (local pH distribution and lixiviant type and concentration, etc.). Herein, mineral occurrence and its associated zeta potential are investigated for EK transport. The new Ek model which is designed to solve the EK flow in complex porous media in a highly parallelizable manner includes three coupled equations: (1) Poisson equation, (2) Nernst–Planck equation, and (3) Navier–Stokes equation. These equations were solved using the lattice Boltzmann method within X-ray computed microtomography images. The proposed model is validated against COMSOL multiphysics in a two-dimensional microchannel in terms of fluid flow behavior when the electrical double layer is both resolvable and unresolvable. A more complex chalcopyrite-silica system is then obtained by micro-CT scanning to evaluate the model performance. The effects of mineral occurrence, zeta potential, and electric potential on the three-dimensional chalcopyrite-silica system were evaluated. Although the positive zeta potential of chalcopyrite can induce a flow of ferric ion counter to the direction of electromigration, the net effect is dependent on the occurrence of chalcopyrite. However, the ion flux induced by electromigration was the dominant transport mechanism, whereas advection induced by electroosmosis made a lower contribution. Overall, a pore-scale EK model is proposed for direct simulation on pore-scale images. The proposed model can be coupled with other geochemical models for full physicochemical transport simulations. Meanwhile, electrokinetic transport shows promise as a human-controllable technique because the electromigration of ions and the applied electric potential can be easily controlled externally. Graphical abstract

Folic Acid and Folinic Acid Protect Hearts of Aging Triple-transgenic Alzheimer’s Disease mice via IGF1R/PI3K/AKT and SIRT1/AMPK Pathways - Da-Tong Ju; Rwei-Fen S. Huang; Bruce Chi-Kang Tsai; Yi-Chen Su; Ping-Ling Chiu; Yung-Ming Chang; V. Vijaya Padma; Tsung-Jung Ho; Chun-Hsu Yao; Wei-Wen Kuo; Chih-Yang Huang (Neurotoxicity Research, 2023)

Transcriptome sequencing reveals the senescence mechanism of ethylene-insensitive cut Rhododendron flowers - Shi-da Xu; Fang Zheng; Xing-min Geng; Zhi-li Jiang; Ling-feng Mao; Jia-le Su (Postharvest Biology and Technology, 2023)

Effects of tillage patterns and stover mulching on N2O production, nitrogen cycling genes and microbial dynamics in black soil - Da-Cheng Hao; Xing-Yuan Su; Hong-Tu Xie; Xue-Lian Bao; Xu-Dong Zhang; Lian-Feng Wang (Journal of Environmental Management, 2023)

Tigliane diterpenoids with cytotoxic activities from Croton damayeshu - Rong-Lin Jia; Qian Liang; Jia-Xin Hu; Si-Da Xie; Xiao-Min Su; Wen-Hui Xu (Phytochemistry Letters, 2023)

Effect of PM2.5 air pollution on the global burden of lower respiratory infections, 1990–2019: A systematic analysis from the Global Burden of Disease Study 2019 - Junjie Hu; Runxuan Zhou; Rong Ding; Da-Wei Ye; Yanbing Su (Journal of Hazardous Materials, 2023)

Robust sugar alcohol with lecithin functionalities for sustainable gelation of edible oils - Eun-Ae Chu; Da-Gyun Park; Eun-Ji Oh; Yeon-Su Lim; Na-Hyeon Kim; Yeong-Min Lee; Kyeong Sik Jin; Jonghoon Choi; Hee-Young Lee (Food Bioscience, 2023)

Two weeks dose range-finding and four weeks repeated dose oral toxicity study of a novel reversible monoamine oxidase B inhibitor KDS2010 in cynomolgus monkeys - Kyung-Tai Kim; Doo-Wan Cho; Jae-woo Cho; Wan-Jung Im; Da-Hee Kim; Jong-Hyun Park; Ki Duk Park; Young-Su Yang; Su-Cheol Han (Toxicological Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Association between ambient air pollutant interaction with kidney function in a large Taiwanese population study - Wei-Yu Su; Da-Wei Wu; Hung-Pin Tu; Szu-Chia Chen; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Science and Pollution Research, 2023)

Octyl gallate targeting the 3C-like protease exhibits highly efficient antiviral activity against swine enteric coronavirus PEDV - Mingjun Su; Baishuang Yin; Xiaoxu Xing; Zijian Li; Jiyu Zhang; Shufeng Feng; Lu Li; Feiyu Zhao; Xu Yang; Shiping Yu; Jun Wang; Yongchen Zhang; et al. (Veterinary Microbiology, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

N-Fluorobenzenesulfonimide as a multifunctional electrolyte additive for co-stabilizing dual-electrodes of lithium metal batteries with enhanced electrochemical performance - Xianjun Weng; Yanyang Qin; Xinyu Da; Yuanjun Zhao; Xuetian Deng; Bo Wen; Manying Cui; Xiangkai Yin; Yaqiong Su; Jiangxuan Song; Shujiang Ding; Xiaofei Hu; et al. (Chemical Engineering Journal, 2023)

Latitudinal responses of the ionosphere over South America during HILDCAA intervals: Case studies - Regia Pereira Silva; Clezio Marcos Denardini; Láysa Cristina Araújo Resende; Juliano Moro; Jonas Sousasantos; Carolina de Sousa do Carmo; Sony Su Chen; Paulo França Barbosa Neto; Giorgio Arlan da Silva Picanço; Jaziel Felipe Braga Campelo; Gilvan Luiz Borba; Marcos Aurélio Ferreira dos Santos (Advances in Space Research, 2023)

Association between air pollutants with calcaneus ultrasound T-score change in a large Taiwanese population follow-up study - Wei-Yu Su; Da-Wei Wu; Szu-Chia Chen; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Science and Pollution Research, 2023)

Understanding gene regulation during the development of the sea cucumber Apostichopus japonicus using comparative transcriptomics - Fang Su; Shilin Liu; Lili Xing; Da Huo; Hongsheng Yang; Lina Sun (Frontiers in Marine Science, 2023)
Embryonic development, especially metamorphosis and settlement, has a major impact on the life history of marine invertebrates. Apostichopus japonicus is an economically important species of sea cucumber. In this study, we performed RNA sequencing on six key stages of A. japonicas development: fertilized eggs, blastula, gastrula, auricularia, doliolaria, and pentactula. A total of 32,353 genes were identified and annotated as a reference gene set for subsequent pairwise comparison analysis. After filtering out low-quality genes, the dynamic molecular responses to development were revealed by WGCNA. The results showed that of the 20 modules, genes in the blue, yellow, and darkslateblue modules were highly correlated with the gastrula, auricularia, and blastula stages, respectively. GO terms for “RNA” and “proteasome complex” were most significantly enriched in the blue module. In the darkslateblue and yellow module, receptors of signaling pathways and metabolic processes were significantly enriched, respectively. All DEGs were categorized into 34 terms, mainly associated with signal transduction and cellular immunity. The expression pattern of genes associated with adhesion, cell cycle, signal, transcription factor, extracellular matrix (ECM), and cytoskeleton was analyzed according to gene function. The results of this study facilitated a more comprehensive understanding of the molecular characteristics of sea cucumber embryonic development and will provide theoretical guidance for larva rearing in sea cucumber culture.

An ensemble mixed spatial model in estimating long-term and diurnal variations of PM2.5 in Taiwan - Pei-Yi Wong; Huey-Jen Su; Shih-Chun Candice Lung; Chih-Da Wu (Science of The Total Environment, 2023)

Egg-yolk-derived carbon dots@albumin bio-nanocomposite as multifunctional coating and its application in quality maintenance of fresh litchi fruit during storage - Xianjie Su; Hetong Lin; Bofei Fu; Shanshan Mei; Mengshi Lin; Hongbin Chen; Zongping Zheng; Hangyu Bo; Da-Peng Yang; Yifen Lin (Food Chemistry, 2023)

Correction: Sepsis Impairs Purkinje Cell Functions and Motor Behaviors Through Microglia Activation - Yue Zhao; Yao Jiang; Ying Shen; Li-Da Su (The Cerebellum, 2023)

Sepsis Impairs Purkinje Cell Functions and Motor Behaviors Through Microglia Activation - Yue Zhao; Yao Jiang; Ying Shen; Li-Da Su (The Cerebellum, 2023)

Genotoxicity assessment of root extracts of Paeonia lactiflora Pall - Su-Min Bak; Seng-Min Back; Da Yeon Kim; Na-Young Jeung; Nan-Young Kim; Jun-Young Yang; Kang-Hyun Han; Yong-Bum Kim; Byung Sun Min; Byoung-Seok Lee; Seong-Hoon Park (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Melatonin improves the removal and the reduction of Cr(VI) and alleviates the chromium toxicity by antioxidative machinery in Rhodobacter sphaeroides - Hao-Tian Mao; Lun-Xing Chen; Meng-Ying Zhang; Qiu-Yun Shi; Hong Xu; Da-Yan Zhang; Zhong-Wei Zhang; Ming Yuan; Shu Yuan; Huai-Yu Zhang; Yan-Qiu Su; Yang-Er Chen (Environmental Pollution, 2023)

ε-Poly( -lysine)-based bioreducible nanogels for mitochondria-targeted delivery and release: Hydrophobicity-tuned nucleus-to-mitochondria organelle-targeting switch and slow disulfide cleavage - Hana Cho; Yeon Su Choi; Da Gyeom Choung; Won Gu Choi; Min Seo Lee; Yong-Yeon Cho; Joo Young Lee; Hye Suk Lee; Han Chang Kang (Chemical Engineering Journal, 2023)

Microfluidic emulsification techniques for controllable emulsion production and functional microparticle synthesis - Wei Wang; Bing-Yu Li; Mao-Jie Zhang; Yao-Yao Su; Da-Wei Pan; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Yousef Faraj; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Temperature and dissolved oxygen influence the immunity, digestion, and antioxidant level in sea cucumber Apostichopus japonicus - Da Huo; Fang Su; Libin Zhang; Hongsheng Yang; Lina Sun (Frontiers in Marine Science, 2022)

Evaluating the survival of Aspergillus niger in a highly polluted red soil with addition of Phosphogypsum and bioorganic fertilizer - Lingzi Meng; Shang Pan; Limin Zhou; Choochad Santasup; Mu Su; Da Tian; Zhen Li (Environmental Science and Pollution Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Biomechanical Changes on the Typical Sites of Pressure Ulcers in the Process of Turning Over from Supine Position: Theoretical Analysis, Simulation, and Experiment - Peng Su; Qinglong Lun; Da Lu; Qiulong Wu; Tian Liu; Leiyu Zhang (Annals of Biomedical Engineering, 2022)

Comparative Analysis of Intestinal Characteristics of Largemouth Bass (Micropterus salmoides) and Intestinal Flora with Different Growth Rates - Xin Su; Da Ji; Junjie Yao; Yuanlong Zou; Mengzhi Yan (Fishes, 2022)
To explore the causes of different growth rates among juvenile populations of largemouth bass, in the present study, a batch of largemouth bass juveniles reared under the same conditions were divided into a fast-growing group and a slow-growing group. We used histological, enzymatic and molecular biology methods to analyze and determine their histomorphological changes, digestive enzyme activity and intestinal floral composition. The fast-growing group had a significantly (p ≤ 0.01) greater intestinal fold height and muscle thickness than the slow-growing group. Lipase activity was significantly (p ≤ 0.01) higher in the fast-growing group than in the slow-growing group. Intestinal microbial analysis showed that the relative abundance of Actinobacteria and Halomonas in the fast-growing group was higher than that in the slow-growing group. This research shows that the differentiation of growth rates in juvenile largemouth bass populations is closely related to intestinal fold status, lipase activity, and intestinal flora.

TREX1 Deficiency Induces ER Stress-Mediated Neuronal Cell Death by Disrupting Ca2+ Homeostasis - Debasish Halder; Su-Jin Jeon; Ji-Yong Yoon; Jeong-Ju Lee; Soo Young Jun; Min-Hyuk Choi; Bohyeon Jeong; Duk Hyun Sung; Da Yong Lee; Byoung Joon Kim; Nam-Soon Kim (Molecular Neurobiology, 2022)
TREX1 is an exonuclease that degrades extranuclear DNA species in mammalian cells. Herein, we show a novel mechanism by which TREX1 interacts with the BiP/GRP78 and TREX1 deficiency triggers ER stress through the accumulation of single-stranded DNA and activates unfolded protein response (UPR) signaling via the disruption of the TREX1-BiP/GRP78 interaction. In TREX1 knockdown cells, the activation of ER stress signaling disrupted ER Ca 2+ homeostasis via the ERO1α-IP3R1-CaMKII pathway, leading to neuronal cell death. Moreover, TREX1 knockdown dysregulated the Golgi-microtubule network through Golgi fragmentation and decreased Ac-α-tubulin levels, contributing to neuronal injury. These alterations were also observed in neuronal cells harboring a TREX1 mutation (V91M) that has been identified in hereditary spastic paraplegia (HSP) patients in Korea. Notably, this mutation leads to defects in the TREX1-BiP/GRP78 interaction and mislocalization of TREX1 from the ER and possible disruption of the Golgi-microtubule network. In summary, the current study reveals TREX1 as a novel regulator of the BiP/GRP78 interaction and shows that TREX1 deficiency promotes ER stress-mediated neuronal cell death, which indicates that TREX1 may hold promise as a therapeutic target for neurodegenerative diseases such as HSP.

PQBP1: A New Player in Metabotropic Glutamate Receptor Signaling and Synaptic Plasticity - Li-Da Su; Ying Shen (Neuroscience Bulletin, 2021)

Implantation of Bone Marrow Mesenchymal Stem Cells into Small Intestinal Submucosa Improves Bile Duct Injury in Rabbits - Ying Li; Piao Wang; Xiao-dong Hu; Jing-da Zeng; Cheng Fang; Yu Gan; Fang-yi Peng; Xiao-li Yang; De Luo; Bo Li; Song Su (Tissue Engineering and Regenerative Medicine, 2021)

Effect of dermal phthalate levels on lung function tests in residential area near a petrochemical complex - Chih-Wen Wang; Szu-Chia Chen; Da-Wei Wu; Huang-Chi Chen; Hung-Hsun Lin; Hung Su; Jen-taie Shiea; Wen-Yi Lin; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Science and Pollution Research, 2021)

Generation of Hepatic Progenitor Cells from the Primary Hepatocytes of Nonhuman Primates Using Small Molecules - Da Hee Hong; Changhee Lee; Yohan Kim; Seung Bum Lee; Su-Cheol Han; Sung Joo Kim; Heung-Mo Yang; Dongho Choi; Jaemin Jeong; Kiyoung Ryu (Tissue Engineering and Regenerative Medicine, 2021)

Stress and Deformation Analysis of Concrete-Facing Sand–Gravel Dam Based on Inversion Parameters - Mingchang Da; Zhengyang Su (Geotechnical and Geological Engineering, 2021)

Large-scale shaking table test on seismic behaviour of anti-slide pile-reinforced bridge foundation and gravel landslide: a case study - Chonglei Zhang; Guanlu Jiang; Da Lei; Aamir Asghar; Lijun Su; Zhimeng Wang (Bulletin of Engineering Geology and the Environment, 2021)

Understanding the dynamical-microphysical-electrical processes associated with severe thunderstorms over the Beijing metropolitan region - Xiushu Qie; Shanfeng Yuan; Zhixiong Chen; Dongfang Wang; Dongxia Liu; Mengyu Sun; Zhuling Sun; Abhay Srivastava; Hongbo Zhang; Jingyu Lu; Hui Xiao; Yongheng Bi; et al. (Science China Earth Sciences, 2021)

Endoplasmic Reticulum Stress Regulates Cardiomyocyte Apoptosis in Myocardial Fibrosis Development via PERK-Mediated Autophagy - Changjiang Zhang; Yuanhong Li; Jingbo Zhao; Ke Su; Ke He; Yurong Da; Hao Xia (Cardiovascular Toxicology, 2020)

Genome-wide investigation of a Korean synthetic breed, Woori-Heukdon using the Illumina PorcineSNP60K BeadChip - Yong-Min Kim; Ha-Seung Seong; Jung-Jae Lee; Da-Hye Son; Jin-Su Kim; Soo-Jin Sa; Young-Sin Kim; Tae-Jeong Choi; Kyu-Ho Cho; Joon-Ki Hong; Jung-Woo Choi; Eun-Seok Cho (Genes & Genomics, 2020)

New land use regression model to estimate atmospheric temperature and heat island intensity in Taiwan - Chin-Yu Hsu; Uen-Ching Ng; Chiao-Ying Chen; Yu-Cheng Chen; Mu-Jean Chen; Nai-Tzu Chen; Shih-Chun Candice Lung; Huey-Jen Su; Chih-Da Wu (Theoretical and Applied Climatology, 2020)

Engineered M13 Peptide Carrier Promotes Angiogenic Potential of Patient-Derived Human Cardiac Progenitor Cells and In Vivo Engraftment - Woong Bi Jang; Seung Taek Ji; Ji Hye Park; Yeon-Ju Kim; Songhwa Kang; Da Yeon Kim; Na-Kyung Lee; Jin Su Kim; Hye Ji Lim; Jaewoo Choi; Thi Hong Van Le; Thanh Truong Giang Ly; et al. (Tissue Engineering and Regenerative Medicine, 2020)

Elastic properties of transversely isotropic rocks containing aligned cracks and application to anisotropy measurement - Song Xu; Yuan-Da Su; Xiao-Ming Tang (Applied Geophysics, 2020)

Large-scale shaking table model test on seismic performance of bridge-pile-foundation slope with anti-sliding piles: a case study - Chonglei Zhang; Guanlu Jiang; Lijun Su; Da Lei; Weiming Liu; Zhimeng Wang (Bulletin of Engineering Geology and the Environment, 2020)

Contrasting the Pb (II) and Cd (II) tolerance of Enterobacter sp. via its cellular stress responses - Zhongquan Jiang; Liu Jiang; Lin Zhang; Mu Su; Da Tian; Tong Wang; Yalin Sun; Ying Nong; Shuijin Hu; Shimei Wang; Zhen Li (Environmental Microbiology, 2020)
Summary Successful application of microorganisms to heavy metal remediation depends on their resistance to toxic metals. This study contrasted the differences of tolerant mechanisms between Pb 2+ and Cd 2+ in Enterobacter sp. Microbial respiration and production of formic acid showed that Enterobacter sp. had a higher tolerant concentration of Pb (>1000 mg l −1 ) than Cd (about 200 mg l −1 ). Additionally, SEM confirmed that most of Pb and Cd nanoparticles (NPs) were adsorbed onto cell membrane. The Cd stress, even at low concentration (50 mg l −1 ), significantly enlarged the sizes of cells. The cellular size raised from 0.4 × 1.0 to 0.9 × 1.6 μm on average, inducing a platelet‐like shape. In contrast, Pb cations did not stimulate such enlargement even up to 1000 mg l −1 . Moreover, Cd NPs were adsorbed homogeneously by almost all the bacterial cells under TEM. However, only a few cells work as ‘hot spots’ on the sorption of Pb NPs. The heterogeneous sorption might result from a ‘self‐sacrifice’ mechanism, i.e., some cells at a special life stage contributed mostly to Pb sorption. This mechanism, together with the lower mobility of Pb cations, caused higher microbial tolerance and removal efficiency towards Pb 2+ . This study sheds evident contrasts of bacterial resistance to the two most common heavy metals.

Cadmium immobilization in aqueous solution by Aspergillus niger and geological fluorapatite - Christopher Uche Okolie; Haoming Chen; Yexin Zhao; Da Tian; Lin Zhang; Mu Su; Zhonquan Jiang; Zhen Li; Huixin Li (Environmental Science and Pollution Research, 2020)

Short bZIP homologue of sulfur regulator Met4 from Ogataea parapolymorpha does not depend on DNA‐binding cofactors for activating genes in sulfur starvation - Su Jin Yoo; Min Jeong Sohn; Da Min Jeong; Hyun Ah Kang (Environmental Microbiology, 2020)
Summary The acquisition of sulfur from environment and its assimilation is essential for fungal growth and activities. Here, we describe novel features of the regulatory network of sulfur metabolism in Ogataea parapolymorpha , a thermotolerant methylotrophic yeast with high resistance to harsh environmental conditions. A short bZIP protein (OpMet4p) of O. parapolymorpha , displaying the combined structural characteristics of yeast and filamentous fungal Met4 homologues, plays a key role as a master regulator of cell homeostasis during sulfur limitation, but also its function is required for the tolerance of various stresses. Domain swapping analysis, combined with deletion analysis of the regulatory domains and genes encoding OpCbf1p, OpMet28p, and OpMet32p, indicated that OpMet4p does not require the interaction with these DNA‐binding cofactors to induce the expression of sulfur genes, unlike the Saccharomyces cerevisiae Met4p. ChIP analysis confirmed the notion that OpMet4p, which contains a canonical bZIP domain, can bind the target DNA in the absence of cofactors, similar to homologues in other filamentous fungi. Collectively, the identified unique features of the O. parapolymorpha regulatory network, as the first report on the sulfur regulation by a short yeast Met4 homologue, provide insights into conservation and divergence of the sulfur regulatory networks among diverse ascomycetous fungi.

Andrographolide enhances hippocampal BDNF signaling and suppresses neuronal apoptosis, astroglial activation, neuroinflammation, and spatial memory deficits in a rat model of chronic cerebral hypoperfusion - Da-Peng Wang; Hang Yin; Qi Lin; Shu-Ping Fang; Jian-Hua Shen; Yi-Fang Wu; Shao-Hua Su; Jian Hai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Application of four-component dipole shear reflection imaging to interpret the geological structure around a deviated well - Sheng-Qing Lee; Ming Chen; Xi-Hao Gu; Yuan-Da Su; Xiao-Ming Tang (Applied Geophysics, 2019)

Modeling δ18O as an early indicator of regime shift arising from salinity stress in coastal vegetation - Su Yean Teh; Hock Lye Koh; Donald L. DeAngelis; Clifford I. Voss; Leonel da Silveira Lobo Sternberg (Hydrogeology Journal, 2019)

Exosomes derived from mesenchymal stem cells inhibit mitochondrial dysfunction-induced apoptosis of chondrocytes via p38, ERK, and Akt pathways - Hui Qi; Dan-Ping Liu; Da-Wei Xiao; Da-Chuan Tian; Yong-Wei Su; Shao-Feng Jin (In Vitro Cellular & Developmental Biology - Animal, 2019)

A new insight into lead (II) tolerance of environmental fungi based on a study of Aspergillus niger and Penicillium oxalicum - Da Tian; Zhongquan Jiang; Liu Jiang; Mu Su; Zheye Feng; Lin Zhang; Shimei Wang; Zhen Li; Shuijin Hu (Environmental Microbiology, 2019)
Summary Environmental microorganisms have been widely applied in heavy metal remediation. This study explored the mechanisms of lead tolerance of two typical filamentous fungi, Aspergillus niger and Penicillium oxalicum . It is shown that the mechanisms of reducing Pb toxicity by these two fungi have three major pathways. The secreted oxalic acid can react with Pb (II) to form insoluble Pb minerals, primarily lead oxalate. Then, the enhanced biosorption via forming new border of cell wall prevents the transportation of Pb (II) into hypha. In addition, the fungal activity could be maintained even at high Pb concentration due to the intracellular accumulation. It was confirmed that A. niger has the higher Pb tolerance (up to 1500 mg l −1 Pb level) compared with P. oxalicum (up to 1000 mg l −1 ). Meanwhile, Pb levels below 1000 mg l −1 partially stimulate the bioactivity of A. niger , which was confirmed by its elevated respiration (from 53 to 63 mg C l −1 medium h −1 ). This subsequently enhanced microbial functions of A. niger to resist Pb toxicity. A better understanding of Pb tolerance of these two fungi sheds a bright future of applying them to remediate lead‐contaminated environments.

Determination of dietary nitrite in patients with esophageal pre-cancerous lesion and normal people: a duplicate diet study - Ting Zhang; Da Pan; Ming Su; Ling-Meng Fu; Cai-Yun Miao; Qing-Yang Yan; Jing Wang; Li-Gang Yang; Shao-Kang Wang; Gui-Ju Sun (Food Additives & Contaminants: Part A, 2018)

Effects of three-dimensional spheroid culture on equine mesenchymal stem cell plasticity - Mi Jeong Park; Jienny Lee; Jeong Su Byeon; Da-Un Jeong; Na-Yeon Gu; In-Soo Cho; Sang-Ho Cha (Veterinary Research Communications, 2018)

Remediation of lead-contaminated water by geological fluorapatite and fungus Penicillium oxalicum - Da Tian; Wenchao Wang; Mu Su; Junyi Zheng; Yuanyi Wu; Shimei Wang; Zhen Li; Shuijin Hu (Environmental Science and Pollution Research, 2018)

BacHBerry: BACterial Hosts for production of Bioactive phenolics from bERRY fruits - Alexey Dudnik; A. Filipa Almeida; Ricardo Andrade; Barbara Avila; Pilar Bañados; Diane Barbay; Jean-Etienne Bassard; Mounir Benkoulouche; Michael Bott; Adelaide Braga; Dario Breitel; Rex Brennan; et al. (Phytochemistry Reviews, 2018)

Synthesis and antiproliferative properties of novel naringenin derivatives - Su-You Liu; Jiang Zeng; Kun-Jian Peng; Li-Chao Zhang; Li-Jun Liu; Zhi-Yong Luo; Da-You Ma (Medicinal Chemistry Research, 2017)

Analysis on shear wave velocity structure of a gravel landslide based on dual-source surface wave method - Xing-qian Xu; Li-jun Su; Guang-da Zhang; Hong-hu Zhu (Landslides, 2017)

Non-Destructive and rapid evaluation of staple foods quality by using spectroscopic techniques: A review - Wen-Hao Su; Hong-Ju He; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2017)

Sublethal effects of imidacloprid on the predatory seven-spot ladybird beetle Coccinella septempunctata - Da Xiao; Jing Zhao; Xiaojun Guo; Hongying Chen; Mengmeng Qu; Weigang Zhai; Nicolas Desneux; Antonio Biondi; Fan Zhang; Su Wang (Ecotoxicology, 2016)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

3D seismic interpretation of subsurface eruptive centers in a Permian large igneous province, Tazhong Uplift, central Tarim Basin, NW China - Jiangfeng Yang; Wenbin Zhu; Da Guan; Beibei Zhu; Liansheng Yuan; Xuemei Xiang; Jinbao Su; Jingwen He; Xinhui Wu (International Journal of Earth Sciences, 2016)

Human amniotic epithelial stem cells promote wound healing by facilitating migration and proliferation of keratinocytes via ERK, JNK and AKT signaling pathways - Bin Zhao; Jia-Qi Liu; Zhao Zheng; Jun Zhang; Shu-Yue Wang; Shi-Chao Han; Qin Zhou; Hao Guan; Chao Li; Lin-Lin Su; Da-Hai Hu (Cell and Tissue Research, 2016)

Downregulation of Glutamate Transporter EAAT4 by Conditional Knockout of Rheb1 in Cerebellar Purkinje Cells - Nan-Wei Jiang; De-Juan Wang; Ya-Jun Xie; Liang Zhou; Li-Da Su; Huashun Li; Qin-Wen Wang; Ying Shen (The Cerebellum, 2016)

Qualitative and Semiquantitative Analysis of Fecal Bifidobacterium Species in Centenarians Living in Bama, Guangxi, China - Fang Wang; Guohong Huang; Da Cai; Danlei Li; Xiaolin Liang; Ting Yu; Peihong Shen; Haiyan Su; Jidong Liu; Hongcang Gu; Mouming Zhao; Quanyang Li (Current Microbiology, 2015)

Simultaneous determination of seven active ingredients in rat plasma by UPLC-MS/MS and application in pharmacokinetic studies after oral administration of scutellaria-coptis herb couple - Le-yue Du; Jian-ming Guo; Da-wei Qian; Er-xin Shang; Shu Jiang; Pei Liu; Shu-lan Su; Fang Zhang; Jin-ao Duan; Jun Xu; Min Zhao (Medicinal Chemistry Research, 2015)

LGI1 is Involved in the Development of Mouse Brain - Li-Da Su; Ya-Jun Xie; Liang Zhou; Ying Shen; Ying-Hong Hu (The Cerebellum, 2015)

Enhancing Nutritional Quality of Silage by Fermentation with Lactobacillus plantarum - Mariadhas Valan Arasu; Min-Woong Jung; Da Hye Kim; Soundharrajan Ilavenil; Mariamichael Jane; Hyung Su Park; Naif Abdullah Al-Dhabi; Byong Tae Jeon; Ki Choon Choi (Indian Journal of Microbiology, 2014)

Regulation of coronaviral poly(A) tail length during infection is not coronavirus species- or host cell-specific - Jui-Hung Shien; Yi-Da Su; Hung-Yi Wu (Virus Genes, 2014)

Positional variation in grain mineral nutrients within a rice panicle and its relation to phytic acid concentration - Da Su; Faisal Sultan; Ning-chun Zhao; Bing-ting Lei; Fu-biao Wang; Gang Pan; Fang-min Cheng (Journal of Zhejiang University-SCIENCE B, 2014)

Expressions of ER, PR, HER-2, COX-2, and VEGF in Primary and Relapsed/Metastatic Breast Cancers - Li Sun; Da-hai Yu; San-Yuan Sun; Shi-Chao Zhuo; Su-sheng Cao; Ling Wei (Cell Biochemistry and Biophysics, 2014)

Construction, characterization and expression of full length cDNA clone of sheep YAP1 gene - Wei Sun; Da Li; Rui Su; Hassan H. Musa; Ling Chen; Hong Zhou (Molecular Biology Reports, 2014)

Study on the In Vitro Effects of the Mixtures of Polycyclic Aromatic Hydrocarbons (PAHs) and Heavy Metals on Ethoxyresorufin-O-Deethylase (EROD) Activity in Mossambica tilapia Liver - Da Xiong Han; Hai Yan Wang; Hong Wei Yue; Su Min Wang (Bulletin of Environmental Contamination and Toxicology, 2013)

Bird species migration ratio in East Asia, Australia, and surrounding islands - Yiliang Kuo; Da-Li Lin; Fu-Man Chuang; Pei-Fen Lee; Tzung-Su Ding (The Science of Nature, 2013)

The First Case of Phaeohyphomycosis Caused by Rhinocladiella basitona in an Immunocompetent Child in China - Qing Cai; Gui-Xia Lv; Yi-Qun Jiang; Huan Mei; Su-Quan Hu; Hong-Bin Xu; Xin-Feng Wu; Yong-Nian Shen; Wei-Da Liu (Mycopathologia, 2013)

Retrograde cPLA2α/Arachidonic Acid/2-AG Signaling Is Essential for Cerebellar Depolarization-Induced Suppression of Excitation and Long-Term Potentiation - Li-Da Su; De-Juan Wang; Dong Yang; Ying Shen; Ying-Hong Hu (The Cerebellum, 2013)

The association between a single nucleotide polymorphism rs11966200 in MHC region and clinical features of generalized vitiligo in Chinese Han population - Jin Tang; Jian Lan Liu; Cheng Zhang; Da Yan Hu; Su Min He; Xian Bo Zuo; Pei Guang Wang; Liang Dan Sun; Xue Jun Zhang; Sen Yang (Molecular Biology Reports, 2013)

Fibroblast growth factor (Fgf) signaling pathway regulates liver homeostasis in zebrafish - Su-Mei Tsai; Da-Wei Liu; Wen-Pin Wang (Transgenic Research, 2013)

ATP Regulates Sodium Channel Kinetics in Pancreatic Islet Beta Cells - Na Zou; Xiao Wu; Yan-Yan Jin; Meng-Zao He; Xin-Xin Wang; Li-Da Su; Marjan Rupnik; Zhen-Yong Wu; Li Liang; Ying Shen (The Journal of Membrane Biology, 2013)

Association between the XRCC3 polymorphisms and breast cancer risk: meta-analysis based on case–control studies - Xiao-Feng He; Wu Wei; Jiao Su; Zi-Xuan Yang; Yi Liu; Ying Zhang; Da-Peng Ding; Wei Wang (Molecular Biology Reports, 2012)

Erratum to: Fisetin induces apoptosis in human cervical cancer HeLa cells through ERK1/2-mediated activation of caspase-8-/caspase-3-dependent pathway - Tsung-Ho Ying; Shun-Fa Yang; Su-Ju Tsai; Shu-Ching Hsieh; Yi-Chang Huang; Da-Tian Bau; Yi-Hsien Hsieh (Archives of Toxicology, 2012)

Fisetin induces apoptosis in human cervical cancer HeLa cells through ERK1/2-mediated activation of caspase-8-/caspase-3-dependent pathway - Tsung-Ho Ying; Shun-Fa Yang; Su-Ju Tsai; Shu-Ching Hsieh; Yi-Chang Huang; Da-Tian Bau; Yi-Hsien Hsieh (Archives of Toxicology, 2012)

Glypican-3, a novel prognostic marker of hepatocellular cancer, is related with postoperative metastasis and recurrence in hepatocellular cancer patients - Su Ning; Chen Bin; Huang Na; Shen Peng; Ding Yi; Ye Xiang-hua; Zeng Fang-yin; Zheng Da-yong; Luo Rong-cheng (Molecular Biology Reports, 2012)

Optimization of Hydrolysis Conditions for the Production of the Angiotensin-I Converting Enzyme Inhibitory Peptides from Sea Cucumber Collagen Hydrolysates - Zun-Ying Liu; Da Chen; Yi-Cheng Su; Ming-Yong Zeng (Journal of Aquatic Food Product Technology, 2011)

Characteristics of CO2 release from forest soil in the mountains near Beijing - Xiang Yang Sun; Cheng Da Gao; Lin Zhang; Su Yan Li; Yong Qiao (Environmental Monitoring and Assessment, 2011)

Cerebellar Long-term Depression is Deficient in Niemann–Pick Type C Disease Mice - Cheng-Long Sun; Li-Da Su; Qiong Li; Xin-Xin Wang; Ying Shen (The Cerebellum, 2011)

An equivalent-tool theory for acoustic logging and applications - Yuan-Da Su; Xiao-Ming Tang; Chuang Hei; Chun-Xi Zhuang (Applied Geophysics, 2011)

Competition between Hardwood Hammocks and Mangroves - Leonel da Silveira Lobo Sternberg; Su Yean Teh; Sharon M. L. Ewe; Fernando Miralles-Wilhelm; Donald L. DeAngelis (Ecosystems, 2007)

Calcineurin differentially regulates fast myosin heavy chain genes in oxidative muscle fibre type conversion - Nuno da Costa; Julia Edgar; Peck-Toung Ooi; Yuhong Su; Joachim D. Meissner; Kin-Chow Chang (Cell and Tissue Research, 2007)

Plant native tryptophan synthase beta 1 gene is a non-antibiotic selection marker for plant transformation - Paoyuan Hsiao; Sanjaya; Ruey-Chih Su; Jaime A. Teixeira da Silva; Ming-Tsair Chan (Planta, 2007)

Characterization of a cDNA coding for an extracellular calmodulin-binding protein from suspension-cultured cells of Angelica dahurica - Guo-Hong Mao; Li-Xia Hou; Cun-Bao Ding; Su-Juan Cui; Da-Ye Sun (Planta, 2005)

Role of tumor metastasis suppressor gene KAI1 in digestive tract carcinomas and cancer cells - Qiao Wu; Yuan Ji; Ming-qing Zhang; Yu-qiang Chen; Fu Chen; Da-lin Shi; Zong-hui Zheng; Yao-jian Huang; Wen-jin Su (Cell and Tissue Research, 2003)